Tribological behavior of doped-DLC coatings in the presence of ionic liquid additives under different lubrication regimes - Sadeghi, Mohammadamin (2023)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia